2020
DOI: 10.1177/0010414019897698
|View full text |Cite
|
Sign up to set email alerts
|

Building Credibility and Cooperation in Low-Trust Settings: Persuasion and Source Accountability in Liberia During the 2014–2015 Ebola Crisis

Abstract: How can governments in low-trust settings overcome their credibility deficit when promoting public welfare? To answer this question, we evaluate the effectiveness of the Liberian government’s door-to-door canvassing campaign during the 2014–2015 Ebola epidemic, which aimed to persuade residents to voluntarily comply with policies for containing the disease. Combining data from an original representative survey of Monrovia during the crisis with variation in the campaign’s reach and using multiple identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 70 publications
1
30
0
8
Order By: Relevance
“…The former yielded two dimensions, referring to trust in authorities and fear of COVID-19. Both confirmed psychological processes widely investigated in the literature on media effects [67,[70][71][72][74][75][76]. The latter identified a single dimension of preventive behaviors toward COVID-19, including avoiding crowded places, using face masks in public spaces, and keeping social distance, in addition to a difference in the use of public transport and working habits.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The former yielded two dimensions, referring to trust in authorities and fear of COVID-19. Both confirmed psychological processes widely investigated in the literature on media effects [67,[70][71][72][74][75][76]. The latter identified a single dimension of preventive behaviors toward COVID-19, including avoiding crowded places, using face masks in public spaces, and keeping social distance, in addition to a difference in the use of public transport and working habits.…”
Section: Discussionsupporting
confidence: 74%
“…Another relevant issue at stake is trust in authorities. Recent research [76] has shown, indeed, that during the 2014-2015 Ebola epidemic, trust in Liberian authorities was a crucial predictor of citizens' compliance with policies for containing the disease.…”
Section: Emotions Elicited By News and Discussion About Covid-19mentioning
confidence: 99%
“…For instance, specialized Ebola treatment facilities that employed community liaisons and social mobilizers to raise awareness and resolve misconceptions were associated with increases in reporting Ebola cases 193 . Correlational evidence from Liberia also suggests that explicit government efforts to reach out to the population, like door-to-door canvassing, are associated with compliance with crisis management policies like bans on gatherings 194 .…”
Section: Cooperation Within Groups Fighting a Global Pandemic Requiresmentioning
confidence: 99%
“…For instance, specialized Ebola treatment facilities which employed community liaisons and social mobilizers to raise awareness and resolve misconceptions, were associated with increases in reporting Ebola cases 195 . Correlational evidence from Liberia also suggests that explicit government efforts to reach out to the population, like door-to-door canvassing, are associated with compliance with crisis management policies like bans on gatherings 196 .…”
Section: Trust and Compliancementioning
confidence: 99%